Attitude and social-adjustment of adopted Filipino children who are members and non- members of a foundation - Somera, Sheilamar G.
Adoption is one of the complex issues the Filipino families and the society face today. This study seeks to give the issue of adoption a whole new light, by discovering the concerns of the adopted children themselves. It aims to answer the following questions: when adoption was disclosed; how adoption was learned by the child; the attitude and feeling he/she has towards his/her adoption; and identify the necessary adjustments they have to undergo. In this study, controlled groups were used to validate the responses given by the interviewees. These responses were based on a structured questionnaire administered by the researcher. The first group of respondents is composed of adopted children who are members of the Adoptive families foundation (AFF). On the other hand, the second set of respondents is composed of adopted children who are not affiliated in any way to any organization or foundation like that of AFF. Key findings indicate that people who knew of the adoption at a younger age showed better social and emotional adjustment than those who earned about it when they were older. Also, knowledge of the adoption learned directly from the adoptive parents resulted to a positive attitude in life. It is interesting to note that respondents who are member of the AFF showed a more positive outlook in life compared to non-members of the AFF that showed negative attitude towards being adopted. With this discovery, the government is recommended to aid in the formation of different organizations and foundations that help not only the adopted child but also his/her adopting parents cope with the uniqueness of their situation.